Geological CO2 Storage Potential in Coal Seam D, South Sumatra Basin - Fadhillah, Tiara; Salinita, Silti; Handoyo, Handoyo (Universitas Islam Negeri Ar-Raniry, 2026)
Rising atmospheric CO₂ emissions from fossil fuel-based industries have intensified the need for effective mitigation strategies, with Carbon Capture and Storage (CCS) in geological formations, particularly un-mined coal seams necessitates specialized research into numerous critical factors that are equivalent thorough characterization of coal properties such as porosity, permeability, uniaxial compressive strength (UCS), poisson ratio, and brittleness. This study serves as a preliminary assessment of the CCS potential of Coal Seam D in the Suban Burung Block, South Sumatra Basin, using drilling data from four wells (within area 960 m × 860 m). This study aims to describe the coal seam D strata for underground CO2 storage. Coal Seam D was identified from core sample data, with laboratory analyses conducted to determine density and porosity values. Then, in this study we predict velocity (Vp and Vs), UCS values, and BI using petrophysical and rock physics approaches. The analysis by integrates well correlation, estimation of elastic and mechanical parameters, and spatial interpolation of petrophysical properties. Results indicate that Coal Seam D has a thickness of 8.1–10.7 m and porosity ranging from 0.14–0.198. Mechanical properties show Uniaxial Compressive Strength (UCS) values of 9.5-9.7 MPa and a Brittleness Index 0.47–0.50 which indicate coal with low to medium strength and medium brittleness. Based on the preliminary analysis, the coal seam D in this region exhibits favorable candidate for implementation CO₂ storage in South Sumatra, Indonesia.